POSISI FORAMEN MENTALIS PADA MAHASISWA SUKU BATAK DITINJAU DARI RADIOGRAFI PANORAMIK DI FKG USU - Cek Dara Manja; Malfi Tunruan Makkelo (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2015)
The position of mental foramen is difficult to determine clinically. However, it can be seen using radiography. The position is generally located below mandibular second premolars, but these positions may vary in each individual. This study aims to know the position of the mental foramen on Bataknese students seen from panoramic radiography in Faculty of Dentistry USU. This research was descriptive with sample of 38 Bataknese students in Faculty of Dentistry USU aged 20-25 years old. The sample taken with purposive sampling methode. The research was conducted in Radiology Department, Faculty of Dentistry USU. The results of research showed that the position of mental foramen on Bataknese students varied, located between the anterior premolars one to first molar mesiobuccal root line. The conclution of this study is the position of the mental foramen on the Bataknese students at faculty of dentistry USU were lysed with second premolar root is equal to 42,1%.